White light LED device based on zwitter-ion ligand passivated perovskite quantum dots and preparation method
The modification of perovskite quantum dots through zwitterionic ligands solves the problems of perovskite quantum dot stability and large-scale production, and realizes efficient and stable preparation of white light LED devices, supporting the commercial application of optoelectronic devices.
Patent Information
- Application Number
- CN202411405520.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-14
AI Technical Summary
The stability of perovskite quantum dots under air and light is limited. Traditional capping molecules lead to surface defects, making it difficult to achieve large-scale production and efficient luminescence. At the same time, traditional synthesis methods are difficult to control crystal growth, affecting their optical performance and stability.
The nucleation and growth process of perovskite quantum dots is controlled by preparing a mixed solution of cesium carbonate and lead acetate trihydrate and reacting with a mixed toluene solution of zwitterionite ligand, and controlling the nucleation and growth process of perovskite quantum dots, combined with centrifugation and drying treatment, a stable perovskite quantum dot phosphor was obtained and mixed with yellow and red phosphors, coated on a blue LED chip to prepare a white LED device.
It significantly improves the stability and optical performance of perovskite quantum dots, achieves efficient and stable white light emission, supports the commercial application of optoelectronic devices, and realizes low-cost preparation for large-scale production.
Smart Images

Figure CN119317255A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of quantum dot display, and particularly relates to a white light LED device based on zwitterionic ligand passivated perovskite quantum dots and a preparation method thereof, which can realize efficient white light emission and low-cost large-scale preparation of white light lighting applications. Background Art
[0002] In recent years, the excellent performance of perovskite materials in optoelectronic applications has attracted widespread attention. As a new type of semiconductor light-emitting material, all-inorganic halide perovskite CsPbX3 (X = Cl, Br and I) quantum dots have shown great potential, especially in high-performance light-emitting diodes, lasers, solar cells and photodetectors. Perovskite quantum dots PeQDs have high photoluminescence quantum yield, tunable PL spectrum and narrow emission linewidth, making them ideal candidates for the next generation of LED technology.
[0003] At present, the research on perovskite quantum dots mainly focuses on optimizing their optical properties and improving their stability. However, these studies still face many challenges. First, the stability of perovskite quantum dots in air and light is limited, which is a major obstacle to their practical application. Traditional capping molecules, such as oleylamine and oleic acid, are prone to induce a large number of surface defects due to weak coordination effects and highly dynamic protonation processes, resulting in poor stability of quantum dots. To this end, researchers are constantly exploring new surface capping ligands to improve the stability of quantum dots. For example, in recent years, a variety of functionalized ligands have been developed, such as ligands containing amino, carboxyl and sulfonic acid groups, which can improve the stability and optical properties of quantum dots to a certain extent, but the ripening problem during crystal growth still exists, resulting in controllable synthesis is still challenging.
[0004] In addition, achieving large-scale production of perovskite quantum dots without sacrificing their luminous efficiency and color purity remains an important technical challenge. Traditional perovskite quantum dot synthesis methods, such as hot injection and solvothermal methods, although they can produce high-quality quantum dots, are difficult to achieve large-scale production. As an emerging synthesis method, ligand-assisted reprecipitation technology has successfully achieved the production of gram-level quantities of perovskite quantum dots by introducing appropriate ligands into the solution to control the nucleation and growth process of quantum dots. However, this technology still needs to solve some problems in practical applications, such as how to further optimize the reaction conditions to improve the optical properties and stability of quantum dots.
[0005] In summary, how to achieve large-scale production of perovskite quantum dots on the basis of achieving efficient luminescence and stability, and how to maintain their excellent performance in practical applications are still hot topics and difficulties in current research. With the continuous deepening of research, the potential of perovskite quantum dots in the field of optoelectronic applications will be further exerted, especially in the fields of high-efficiency white light LEDs, and are expected to be more widely used. Perovskite quantum dots (structural formula: CsPbX3, where X=Cl, Br, I) are an emerging luminescent material with high fluorescence quantum yield, adjustable fluorescence emission peaks and other excellent optical properties, making them a material with great application prospects in the fields of lighting and display. However, due to its own characteristics, perovskite quantum dots are easily affected by the external environment, which seriously damages the luminescence performance and stability, hindering the practical application of this material. Summary of the invention
[0006] In view of the deficiencies in the prior art, the present invention provides a white light LED device based on zwitterionic ligand passivated perovskite quantum dots and a preparation method, so as to improve the fluorescence efficiency and stability of the perovskite quantum dots, realize the large-scale preparation of perovskite quantum dots, and obtain a high-efficiency and low-cost white light LED device.
[0007] The technical solution provided by the present invention is as follows:
[0008] The present invention provides a method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, comprising the following steps: S1, preparing a cesium carbonate n-butyric acid mixed solution, a lead acetate trihydrate n-butyric acid mixed solution, a tetra-n-octylammonium bromide toluene solution and a zwitterionic ligand n-butyric acid mixed toluene solution; S2, adding a mixed solution of lead acetate trihydrate and n-butyric acid and a mixed solution of cesium carbonate and n-butyric acid to a mixed toluene solution of zwitterionic ligand n-butyric acid in sequence, stirring to obtain a precursor, and then adding a toluene solution of tetra-n-octylammonium bromide to the precursor to react to obtain a stock solution of perovskite quantum dots modified with zwitterionic ligands; S3, centrifuging the perovskite quantum dot stock solution to obtain a precipitate, and drying the precipitate to obtain a pure perovskite quantum dot phosphor; S4, mixing the perovskite quantum dot phosphor with the yellow phosphor and the red phosphor, adding the mixture into the mixed organic silica gel and stirring evenly to obtain a mixture; S5. The mixture is coated on a blue light LED chip using a 450 nm wavelength laser as an excitation light source, and the white light LED device is obtained after curing.
[0009] Furthermore, both S1 and S2 are performed at room temperature.
[0010] Furthermore, the molar ratio of cesium carbonate to n-butyric acid is 0.15:20-25, the molar ratio of lead acetate trihydrate to n-butyric acid is 0.3:80-100, and the molar ratio of zwitterionic ligand to n-butyric acid is 0.3:20-25.
[0011] Furthermore, the volume ratio of the lead acetate trihydrate n-butyric acid mixed solution, the cesium carbonate n-butyric acid mixed solution, the zwitterionic ligand n-butyric acid mixed toluene solution and the tetra-n-octylammonium bromide toluene solution is 2:0.8~1:14:1.
[0012] Furthermore, in S2, the reaction time of adding the mixed solution of lead acetate trihydrate and n-butyric acid and the mixed solution of cesium carbonate and n-butyric acid to the mixed toluene solution of zwitterionic ligand n-butyric acid in sequence is 5 to 10 minutes, and the reaction time of adding the toluene solution of tetra-n-octylammonium bromide to the precursor is 1 to 2 minutes.
[0013] Furthermore, the centrifugal agent used for centrifugation in S3 is ethyl alcohol, the volume ratio of the centrifugal agent to the perovskite quantum dot stock solution is 2-2.5:1, and the drying is carried out in a vacuum drying oven at 40-70°C for 12-24 h.
[0014] Furthermore, the mixed organic silica gel in S4 includes organic silica gel A and organic silica gel B in a volume ratio of 1-1.2:2, and the mass ratio of the perovskite quantum dot phosphor, the yellow phosphor and the red phosphor is 5-6:5:1.
[0015] Furthermore, the average size of the perovskite quantum dots is 9-12 nm, the fluorescence emission peak of the perovskite quantum dots is 510-520 nm, and the color coordinate x value and y value of the white light LED device are both 0.33.
[0016] Furthermore, the zwitterionic ligand is N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt.
[0017] The present invention also provides a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, which is prepared according to the above-mentioned preparation method.
[0018] Beneficial Effects
[0019] The present invention effectively inhibits the ripening process of perovskite quantum dots by introducing zwitterionic ligands in the synthesis, and successfully controls the size growth of quantum dots. Zwitterionic ligands can bind more closely to the surface of perovskite quantum dots, effectively passivate surface defects, significantly enhance the stability of quantum dots, and improve their optical properties, thereby achieving efficient and stable luminescence. In addition, the present invention optimizes the synthesis method, and a one-step method at room temperature achieves the mass preparation of efficient and stable perovskite quantum dots. The powder material obtained after drying can be used to make high-efficiency white LEDs, providing reliable technical support for the commercial application of optoelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a fluorescence emission spectrum of CsPbBr3 perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in Example 1 of the present invention;
[0021] Figure 2 The ultraviolet absorption spectrum of CsPbBr3 perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in Example 1 of the present invention;
[0022] Figure 3 This is an X-ray diffraction pattern of CsPbBr3 perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in Example 1 of the present invention;
[0023] Figure 4 This is a transmission electron micrograph of CsPbBr3 perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in Example 1 of the present invention;
[0024] Figure 5 This is a storage stability diagram of CsPbBr3 perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in Example 1 of the present invention;
[0025] Figure 6 This is a picture of the CsPbBr3 perovskite quantum dot phosphor modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in large quantities in Example 2 of the present invention;
[0026] Figure 7 This is a thermogravimetric analysis diagram of the CsPbBr3 perovskite quantum dot phosphor modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt prepared in large quantities in Example 2 of the present invention;
[0027] Figure 8This is a device structure diagram of a white light emitting LED chip prepared in Example 2 of the present invention;
[0028] Fig. 9 This is a spectrum diagram of the white light LED prepared in Example 2 of the present invention;
[0029] Fig.10 This is the color coordinate diagram of the white light LED prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0030] The present invention is further explained below in conjunction with specific implementation cases.
[0031] The embodiment of the present invention provides a method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, comprising the following steps: S1, preparing a cesium carbonate n-butyric acid mixed solution, a lead acetate trihydrate n-butyric acid mixed solution, a tetra-n-octylammonium bromide toluene solution and a zwitterionic ligand n-butyric acid mixed toluene solution; S2, adding a mixed solution of lead acetate trihydrate and n-butyric acid and a mixed solution of cesium carbonate and n-butyric acid to a mixed toluene solution of zwitterionic ligand n-butyric acid in sequence, stirring to obtain a precursor, and then adding a toluene solution of tetra-n-octylammonium bromide to the precursor to react to obtain a stock solution of perovskite quantum dots modified with zwitterionic ligands; S3, centrifuging the perovskite quantum dot stock solution to obtain a precipitate, and drying the precipitate to obtain a pure perovskite quantum dot phosphor; S4, mixing the perovskite quantum dot phosphor with the yellow phosphor and the red phosphor, adding the mixture into the mixed organic silica gel and stirring evenly to obtain a mixture; S5. The mixture is coated on a blue light LED chip using a 450 nm wavelength laser as an excitation light source, and the white light LED device is obtained after curing.
[0032] In this embodiment, S1 and S2 are both performed at room temperature.
[0033] In this embodiment, the molar ratio of cesium carbonate to n-butyric acid is 0.15:20-25, the molar ratio of lead acetate trihydrate to n-butyric acid is 0.3:80-100, and the molar ratio of zwitterionic ligand to n-butyric acid is 0.03:20-25.
[0034] In this embodiment, the volume ratio of the lead acetate trihydrate n-butyric acid mixed solution, the cesium carbonate n-butyric acid mixed solution, the zwitterionic ligand n-butyric acid mixed toluene solution and the tetra-n-octylammonium bromide toluene solution is 2:0.8~1:14:1.
[0035] In this embodiment, the reaction time of adding the lead acetate trihydrate n-butyric acid mixed solution and the cesium carbonate n-butyric acid mixed solution to the zwitterionic ligand n-butyric acid mixed toluene solution in S2 is 5 to 10 minutes, and the reaction time of adding the tetra-n-octylammonium bromide toluene solution to the precursor is 1 to 2 minutes.
[0036] In this embodiment, the centrifugal agent used for centrifugation in S3 is ethyl alcohol, the volume ratio of the centrifugal agent to the perovskite quantum dot stock solution is 2:1, and the drying is carried out in a vacuum drying oven at 40-70°C for 12-24 h.
[0037] In this embodiment, the mixed organic silica gel in S4 includes organic silica gel A and organic silica gel B in a volume ratio of 1:2, and the mass ratio of the perovskite quantum dot phosphor, the yellow phosphor and the red phosphor is 5-6:5:1.
[0038] In this embodiment, the average size of the perovskite quantum dots is 9-12 nm, the fluorescence emission peak of the perovskite quantum dots is 510-520 nm, and the color coordinate x value and y value of the white light LED device are both 0.33.
[0039] In this embodiment, the zwitterionic ligand is N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt.
[0040] The embodiment of the present invention also provides a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, which is prepared according to the preparation method described above.
[0041] Example 1
[0042] The embodiment of the present invention provides a preparation method of perovskite quantum dots based on zwitterionic ligand passivation, comprising the following steps:
[0043] 1) 0.15 mmol of cesium carbonate and 2 mL of n-butyric acid were mixed, stirred at room temperature for 10 min, and a cesium carbonate n-butyric acid mixed solution was obtained when the solution was completely transparent. The molar ratio of cesium carbonate to n-butyric acid was 0.15:22.
[0044] 2) 0.03 mmol of lead acetate trihydrate and 4 mL of n-butyric acid were mixed, stirred at room temperature for 10 min, and a lead acetate trihydrate n-butyric acid mixed solution was obtained when the solution was completely transparent. The molar ratio of lead acetate trihydrate to n-butyric acid was 0.3:44.
[0045] 3) Mix 1.8 mmol of tetra-n-octylammonium bromide and 4 mL of toluene, stir at room temperature for 1-2 h, and obtain a tetra-n-octylammonium bromide toluene solution when the solution becomes completely transparent.
[0046] 4) 0.03 mmol of N, N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, 2 mL of n-butyric acid and 5 mL of toluene were mixed and stirred at room temperature for 10 min. When the solution was completely transparent, a zwitterionic ligand n-butyric acid mixed toluene solution was obtained. The molar ratio of the N, N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt to n-butyric acid was 0.03:22.
[0047] 5) 1 mL of trihydrate lead acetate n-butyric acid mixture and 0.5 mL of cesium carbonate n-butyric acid mixture were added to the zwitterionic ligand n-butyric acid mixed toluene solution in sequence, and stirred at room temperature for 5 min to obtain the final precursor. 0.5 mL of tetra-n-octylammonium bromide toluene solution was injected into the above precursor and reacted for 1 min to obtain the zwitterionic ligand modified perovskite quantum dot stock solution.
[0048] 6) Add the obtained quantum dot original solution into a centrifuge tube and add ethyl acetate twice the volume of the original solution. Centrifuge at 10,000 r / min for two minutes. After the centrifugation, pour out the supernatant and add 3 ml of toluene to the precipitate. After the centrifuge tube is shaken and the precipitate is completely dissolved, centrifuge at 8,000 r / min for two minutes. The supernatant obtained is the pure green-luminescent CsPbBr3 perovskite quantum dot product.
[0049] like Figure 1 The figure shows the fluorescence emission spectrum of perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, with an emission wavelength of 520 nm. Figure 2 The figure shows the UV absorption spectrum of perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, and its absorption peak is consistent with the fluorescence emission spectrum. Figure 3 The figure shows the X-ray diffraction pattern of perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, which shows the high crystallinity of the sample and indicates that the sample is a standard monoclinic perovskite crystal. Figure 4 The figure shows a transmission electron micrograph of perovskite quantum dots modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt. The average size is about 10.7 nm, and the size is relatively uniform. In order to test the stability of the product, we stored the product indoors and tested the changes in luminescence intensity, such as Figure 5 As shown, after 100 days of storage, the luminous intensity can still be maintained at about 80% of the initial intensity.
[0050] Example 2
[0051] The embodiment of the present invention provides a method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, comprising the following steps:
[0052] 1) 1.875 mmol of cesium carbonate and 25 mL of n-butyric acid were mixed, stirred at room temperature for 10 min, and a cesium carbonate n-butyric acid mixed solution was obtained when the solution was completely transparent. The molar ratio of cesium carbonate to n-butyric acid was 0.15:22.
[0053] 2) 0.375 mmol of lead acetate trihydrate and 50 mL of n-butyric acid were mixed, stirred at room temperature for 10 min, and a lead acetate trihydrate n-butyric acid mixed solution was obtained when the solution was completely transparent. The molar ratio of lead acetate trihydrate to n-butyric acid was 0.3:44.
[0054] 3) Mix 11.25 mmol of tetra-n-octylammonium bromide and 25 mL of toluene, stir at room temperature for 1 to 2 h, and obtain a tetra-n-octylammonium bromide toluene solution when the solution becomes completely transparent.
[0055] 4) 1.5 mmol of N, N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, 100 mL of n-butyric acid and 250 mL of toluene were mixed and stirred at room temperature for 10 min. When the solution was completely transparent, a zwitterionic ligand n-butyric acid mixed toluene solution was obtained. The molar ratio of the N, N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt to n-butyric acid was 0.03:22.
[0056] 5) 50 mL of trihydrate lead acetate n-butyric acid mixture and 25 mL of cesium carbonate n-butyric acid mixture were added to the zwitterionic ligand n-butyric acid mixed toluene solution in sequence, and stirred at room temperature for 5 min to obtain the final precursor. 25 mL of tetra-n-octylammonium bromide toluene solution was injected into the above precursor and reacted for 1 min to obtain the zwitterionic ligand modified perovskite quantum dot stock solution.
[0057] 6) Add the obtained quantum dot original solution to a centrifuge tube and add ethyl acetate twice the volume of the original solution, centrifuge at 10000 r / min for two minutes, pour out the supernatant after centrifugation, place the precipitate in a vacuum drying oven at 40°C and dry for 24 hours to obtain pure green luminescent CsPbBr3 perovskite quantum dot phosphor. Figure 6 The figure shows the large-scale preparation of CsPbBr3 perovskite quantum dot phosphor modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt; Figure 7 Shown is the thermogravimetric analysis of CsPbBr3 perovskite quantum dot phosphor modified with N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt, and its yield is calculated to be 69%.
[0058] 7) 50 mg of organic silica gel A (organic silica gel ZWL8820H A; Shenzhen looking long technology co., LTD) and 200 mg of organic silica gel B (organic silica gel ZWL8820H B; Shenzhen looking long technology co., LTD) were fully stirred to obtain mixed organic silica gel, and then 60 mg of green perovskite quantum dot phosphor and 50 mg of Y3Al5O 12 :Ce yellow phosphor and 10 mg CaAlSiN3:Eu red phosphor are added to the mixed organic silica gel and stirred thoroughly. The mixed organic silica gel containing the mixed phosphor is applied to a 450 nm blue LED chip, and the organic encapsulated silica gel is solidified by annealing at 100°C for one hour to obtain a high-performance white light emitting LED chip. The device structure of the chip is as follows: Figure 8 As shown, the blue LED is used as an excitation light source to excite the phosphor mixed coating to emit light, and then emit white light through combination. Fig. 9 The figure shows the spectrum of the prepared white light LED, from which we can see the emission peak of the blue chip (452 nm) and the emission peak of the green quantum dot phosphor (520 nm). Fig.10 Shown is the color coordinate diagram of the prepared white light LED, whose color coordinate value is (0.33, 0.33).
[0059] The synthesis mechanism of the present invention is as follows: nanocrystals are prepared by different solubility of compounds in different solvents, and the size and morphology of nanocrystals are controlled by surface ligands, so as to obtain perovskite quantum dots with controllable emission wavelength. The concentration and proportion of the precursor solution determine the composition and stoichiometric ratio of the perovskite quantum dots, thereby affecting its crystal structure and optical properties. Generally speaking, a high-concentration precursor solution will lead to rapid nucleation and growth, producing larger perovskite quantum dots; a low-concentration precursor solution will lead to slow nucleation and growth, producing smaller perovskite quantum dots. The nucleation reaction is completed within about 5 to 10 seconds, and the organic ligands in the reaction solution will control the growth rate of the perovskite quantum dots in this process, so that they have a uniform size distribution, and obtain perovskite quantum dots of ideal size. After the reaction is completed, some organic ligands will be adsorbed on the surface of the perovskite quantum dots, passivate the surface defects of the perovskite quantum dots, and improve the fluorescence luminescence efficiency and stability of the perovskite quantum dots.
[0060] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots, characterized in that: The following steps are involved: S1, preparing a cesium carbonate n-butyric acid mixed solution, a lead acetate trihydrate n-butyric acid mixed solution, a tetra-n-octylammonium bromide toluene solution and a zwitterionic ligand n-butyric acid mixed toluene solution; S2, adding a mixed solution of lead acetate trihydrate and n-butyric acid and a mixed solution of cesium carbonate and n-butyric acid to a mixed toluene solution of zwitterionic ligand n-butyric acid in sequence, stirring to obtain a precursor, and then adding a toluene solution of tetra-n-octylammonium bromide to the precursor to react to obtain a stock solution of perovskite quantum dots modified with zwitterionic ligands; S3, centrifuging the perovskite quantum dot stock solution to obtain a precipitate, and drying the precipitate to obtain a pure perovskite quantum dot phosphor; S4, mixing the perovskite quantum dot phosphor with the yellow phosphor and the red phosphor, adding the mixture into the mixed organic silica gel and stirring evenly to obtain a mixture; S5. The mixture is coated on a blue light LED chip using a 450 nm wavelength laser as an excitation light source, and the white light LED device is obtained after curing.
2. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: Both S1 and S2 are performed at room temperature.
3. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The molar ratio of cesium carbonate to n-butyric acid is 0.15:20-25, the molar ratio of lead acetate trihydrate to n-butyric acid is 0.3:80-100, and the molar ratio of zwitterionic ligand to n-butyric acid is 0.03:20-25.
4. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The volume ratio of the lead acetate trihydrate n-butyric acid mixed solution, the cesium carbonate n-butyric acid mixed solution, the zwitterionic ligand n-butyric acid mixed toluene solution and the tetra-n-octylammonium bromide toluene solution is 2:0.8~1:14:
1.
5. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: In S2, the reaction time of adding the mixed solution of lead acetate trihydrate and n-butyric acid and the mixed solution of cesium carbonate and n-butyric acid to the mixed toluene solution of zwitterionic ligand n-butyric acid in sequence is 5-10 minutes, and the reaction time of adding the toluene solution of tetra-n-octylammonium bromide to the precursor is 1-2 minutes.
6. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The centrifugal agent used for centrifugation in S3 is ethyl alcohol, and the volume ratio of the centrifugal agent to the perovskite quantum dot stock solution is 2-2.5:
1. The drying is carried out in a vacuum drying oven at 40-70°C for 12-24 h.
7. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The mixed organic silica gel in S4 includes organic silica gel A and organic silica gel B in a volume ratio of 1-1.2:2, and the mass ratio of the perovskite quantum dot phosphor, the yellow phosphor and the red phosphor is 5-6:5:
1.
8. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The average size of the perovskite quantum dots is 9-12 nm, the fluorescence emission peak of the perovskite quantum dots is 510-520 nm, and the color coordinate x value and y value of the white light LED device are both 0.
33.
9. The method for preparing a white light LED device based on zwitterionic ligand passivated perovskite quantum dots according to claim 1, characterized in that: The zwitterionic ligand is N,N-dimethyl-N-(3-sulfopropyl)-1-octadecyl ammonium inner salt.
10. A white light LED device based on zwitterionic ligand passivated perovskite quantum dots, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.